2016
DOI: 10.1007/978-981-10-2553-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Relationship Between Home and Family Experiences and Young Children’s Early Numeracy Learning

Abstract: This chapter includes analyses of the relationships between informal and formal home and family early numeracy learning experiences and preschool children's mathematics performance. The research synthesis consisted of 13 samples of children between 36 and 84 months of age (Median age = 69 months). The 13 samples comprised more than 5000 children and their parents or other primary caregivers. Results showed that variations in the children's early numeracy experiences are associated with variations in the childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 44 publications
8
69
2
1
Order By: Relevance
“…These researchers have found positive links between home numeracy activities and children's skills. Other studies, however, have not found links between the HNE and children's numeracy skills (see Dunst, Hamby, Wilkie, & Dunst, 2017, for a meta-analysis; Elliott & Bachman, 2017). Elliott and Bachman (2017) outline several possible reasons for the variability of findings in the field of HNE, including a heavy reliance on parents' selfreports, failure to test the direction of the relations between children's performance and the home environment, a preponderance of small heterogeneous samples, few studies conducted outside of Westernized countries, limited or variable (across studies) assessment of home environments, untested interactions between parent characteristics and home activities, and an emphasis on concurrent studies, usually of children in preschool, kindergarten, or Grade 1.…”
Section: The Hnementioning
confidence: 95%
See 1 more Smart Citation
“…These researchers have found positive links between home numeracy activities and children's skills. Other studies, however, have not found links between the HNE and children's numeracy skills (see Dunst, Hamby, Wilkie, & Dunst, 2017, for a meta-analysis; Elliott & Bachman, 2017). Elliott and Bachman (2017) outline several possible reasons for the variability of findings in the field of HNE, including a heavy reliance on parents' selfreports, failure to test the direction of the relations between children's performance and the home environment, a preponderance of small heterogeneous samples, few studies conducted outside of Westernized countries, limited or variable (across studies) assessment of home environments, untested interactions between parent characteristics and home activities, and an emphasis on concurrent studies, usually of children in preschool, kindergarten, or Grade 1.…”
Section: The Hnementioning
confidence: 95%
“…In general, the term formal refers to experiences that have a didactic focus, where parents intentionally choose activities in which they teach their children specific math-related skills, such as mental addition or recognizing numbers (LeFevre et al, 2009). Some authors have further differentiated formal experiences into basic or mapping and advanced or operational activities (Dunst et al, 2017;Skwarchuk et al, 2014;Susperreguy et al, 2018). Mapping activities are those in which parents focus on teaching simple numerical activities related to the different ways of representing numbers (e.g., identifying numbers).…”
Section: Numeracy Activitiesmentioning
confidence: 99%
“…A recent meta-analysis finds that informal, basic numeracy activities are better predictors of children's mathematics achievements than formal numeracy activities (Dunst, Hamby, Wilkie, & Dunst, 2017). Skwarchuk et al's (2014) model, however, indicates that parental numeracy attitudes, informal numeracy tools, and formal numeracy activities have effects on children's mathematics knowledge or skills; on the other hand, the effects of basic numeracy activities on learning outcomes are not significant, which may be because informal numeracy tools are included in their model.…”
Section: Rationalesmentioning
confidence: 96%
“…Rationales. Past research only focuses on the effect of early numeracy activities on cognitive outcomes, mainly mathematics achievement or skills (Dunst et al, 2017;Skwarchuk et al, 2014). There appears to be no research to date addressing the issue of the effect of early numeracy activities on affective outcomes.…”
Section: Multiple Effects Of Early Numeracy Activities On Achievementmentioning
confidence: 99%
“…Principles of family-centered care (FCC) suggest that occupational therapy practitioners work as partners with families in addressing their goals and priorities rather than the therapist's goals (Kuo et al, 2012). FCC is considered best practice and an important method in promoting positive outcomes related to family functioning (Dunst, Hamby, & Brookfield, 2007;Kuo et al, 2012). An occupational therapist can provide assistance with many of the commonly reported challenging behaviors in ASD, such as escapism, inappropriate sexual behaviors, and poor object play (Jang et al, 2011;Kuhaneck & Britner, 2010), through basic occupational therapy processes of task analysis, task-environment modification and adaptation, and client-family education practices.…”
Section: Call To Actionmentioning
confidence: 99%